USLŪB WA I'JĀZ AL-QUR' ĀN IN SŪRAH AN-NĀZI'ĀT - Azizah, Balkis Nur Azizah; Al Jufri, Moh. Iza; Muassomah (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
Uslūb wa i'jāz al-Qur'ān, in general, is a style of language used in the Qur'ān by classifying and analyzing in detail through the i'jāz factors or miracles contained in the Qur'ān so that the formulation of the problem in this study is 1) what are the forms of i'jāz balāgȳ what happened in the surat an-Nāzi'āt, and 2) what are the forms of i'jāz 'ilmi in the sūrah an-Nāzi'āt. This study uses a descriptive qualitative approach based on the text of the Qur'ān based on the object's selection. This study intends to analyze the style of language and its form using the uslūb wa i'jāz al-Qur'ān analysis approach. Problem-solving is done by presenting the results based on the facts that match what is from the sūrah an-Nāzi'āt. Data was collected using reading and note-taking techniques. Furthermore, the results found were that there were two forms of i'jāz balāgȳ, namely uslūb badī' saja', uslūb badi' muṭābaqah and badī' jinās isytiqāq. There were three aspects of i'jāz 'ilmi in the form supernatural, scientific, and historical matters.